Fractalkine (CX3CL1) and Its Receptor CX3CR1: A Promising Therapeutic Target in Chronic Kidney Disease? - Cormican, Sarah; Griffin, Matthew D. (Frontiers in Immunology, 2021)
Innate immune cells are key contributors to kidney inflammation and fibrosis. Infiltration of the renal parenchyma by innate immune cells is governed by multiple signalling pathways. Since the discovery of the chemokine fractalkine (CX3CL1) and its receptor, CX3CR1 over twenty years ago, a wealth of evidence has emerged linking CX3CL1-CX3CR1 signalling to renal pathologies in both acute and chronic kidney diseases (CKD). However, despite the extent of data indicating a pathogenic role for this pathway in kidney disease and its complications, no human trials of targeted therapeutic agents have been reported. Although acute autoimmune kidney disease is often successfully treated with immunomodulatory medications, there is a notable lack of treatment options for patients with progressive fibrotic CKD. In this article we revisit the CX3CL1-CX3CR1 axis and its functional roles. Furthermore we review the accumulating evidence that CX3CL1-CX3CR1 interactions mediate important events in the intra-renal pathophysiology of CKD progression, particularly via recruitment of innate immune cells into the kidney. We also consider the role that systemic activation of the CX3CL1-CX3CR1 axis in renal disease contributes to CKD-associated cardiovascular disease. Based on this evidence, we highlight the potential for therapies targeting CX3CL1 or CX3CR1 to benefit people living with CKD.